Implementation of Learning Using Whatsap Based on A Scientific Approach to Improve Indonesian Learning Outcomes in Primary School Students - Hartanto, Slamet (Universitas Sebelas Maret, 2020)
This study aims to improve the learning outcomes of Indonesian class V SDN 2 Bendo using WhattsApp with a scientific approach. This research is a classroom action research with four main steps, namely: planning, acting, observing and reflecting. Collecting data in this study using observation and tests. The data collected was then analyzed and it can be concluded that the application of learning using Whatsapp based on a scientific approach can: (1) Improve the learning outcomes of class V students of SDN 2 Bendo, Nogosari District, Boyolali Regency, Semester I of the 2020/2021 academic year of 28.6% in pre cycle to 42.8% in cycle I, 71.4% in cycle II and in cycle III increased to 100%. (2) The steps for implementing Whatsapp Social Media Based on the Scientific Approach can improve learning outcomes in Indonesian for Class V SDN 2 Bendo, Nogosari District, Boyolali Regency, Semester I of the 2020/2021 Academic Year. These steps include Observing, Asking, Trying, Reasoning, and Communicating